An approach to the electroanalysis of electrode passivating analytes: the determination of phenol - Compton, RG; Wang, Y (Wiley, 2020)
The electrode‐passivating species, phenol, was electrochemically determined by using semicircular sweep voltammetry on a basal‐plane pyrolytic graphite (BPPG) electrode. The electrode fouling caused by the polymerization of phenol was prevented at low concentrations by introducing a second species, 4‐amino‐2,6‐dichlorophenol (PAP), to prevent the polymerization of phenol in the vicinity of the electrode surface. Semicircular sweep voltammetry was used to amplify the analytical signal, realizing the detection of phenol in the concentration range of 25–800 μM without problems of electrode fouling.